2012
DOI: 10.1016/j.jmoldx.2012.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The Germline MLH1 K618A Variant and Susceptibility to Lynch Syndrome-Associated Tumors

Abstract: Missense variants discovered during sequencing of cancer susceptibility genes can be problematic for clinical interpretation. MLH1 K618A, which results from a 2-bp alteration (AAG¡GCG) leading to a substitution of lysine to alanine in codon 618, has variously been interpreted as a pathogenic mutation, a variant of unknown significance, and a benign polymorphism. We evaluated the role of MLH1 K618A in predisposition to cancer by genotyping 1512 control subjects to assess its frequency in the general population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
1
4
1
Order By: Relevance
“…The classification of MLH1 c.1852_1853delAAinsGC p.(Lys618Ala) is a contentious issue with some functional assays suggesting reduced protein function [Belvederesi et al., ; Blasi et al., ; Guerrette et al., ; Kondo et al., ; Perera and Bapat, ], but family studies (including this study) indicating it is not pathogenic [Castillejo et al., ]. Consistent with these inconclusive findings, a recent case–control study concluded that the variant was not fully penetrant, and was associated with a twofold increase in risk of Lynch syndrome‐associated tumors [Medeiros et al., ].…”
Section: Discussionsupporting
confidence: 70%
“…The classification of MLH1 c.1852_1853delAAinsGC p.(Lys618Ala) is a contentious issue with some functional assays suggesting reduced protein function [Belvederesi et al., ; Blasi et al., ; Guerrette et al., ; Kondo et al., ; Perera and Bapat, ], but family studies (including this study) indicating it is not pathogenic [Castillejo et al., ]. Consistent with these inconclusive findings, a recent case–control study concluded that the variant was not fully penetrant, and was associated with a twofold increase in risk of Lynch syndrome‐associated tumors [Medeiros et al., ].…”
Section: Discussionsupporting
confidence: 70%
“…Regarding its putative implication in familial CRC, this variant was also seen to be over-represented in families with suspected Lynch syndrome in a previous study [29]. Our results will be not in agreement with this previous observation since the K618A variant was not linked in the Epicolon cohort to the presence of CRC family history and Lynch syndrome family history.…”
Section: Resultscontrasting
confidence: 86%
“…In similar vein, the T allele of a functional C/T polymorphism (rs11024595) in the promoter region of the SAA1 gene is significantly over-represented in familial Mediterranean fever patients as compared with normal controls (Migita et al 2013). The MLH1 Lys618Ala mutation (AAG>GCG; rs35502531), initially supposed to be a benign polymorphism, has been found to be significantly over-represented in sporadic cancers associated with Lynch syndrome; MLH1 Ala618 appears to have a reduced ability to bind PMS2, one of the MLH1 protein’s mismatch repair partners (Medeiros et al 2012). Finally, the functional KCNE1 Asp85Asn polymorphism (rs1805128), which occurs in the general population with a frequency of 0.8 %, occurs at a frequency of 3.9 % in long QT syndrome patients (Nishio et al 2009).…”
Section: Modulating Influence Of Additional Allelic Variants In Cis Omentioning
confidence: 99%